DAMPAK KEBIJAKAN PEMBANGUNAN INSFRASTRUKTUR DI KOTA MALANG - Muhammad Okto Adhitama; Imam Hanafi (REFORMASI, 2014)
Malang which is rapidly grown forces mass mobility in large scale and it is absolutely correlated to the growing number of transportation device to serve the society that use public transportation service. Replacement of the terminal is also a draw considering the Tower next to the terminal there is a very crowded market in the city of Malang Main Market Tower. This study used a qualitative method because it is felt this is a suitable method to search for an existing phenomenon. The interesting phenomenon of this study is the congestion and chaos that became a routine when a bus or public transportation in both the city and between the city will enter or exit the Terminal Hamid Rusdi. This is compounded by the habit of putting the cart vendors selling or even selling at a roadside place where many of these vehicles. Not only that, the congestion that often occurs at the junction of former Terminal Tower is due to the implementation of one-way doors. Cars in the city or intercity transportation in and out of the same access road. with two different purposes, in city and intercity, which is supposed to have access to different doors.